1994
DOI: 10.1248/bpb.17.1193
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Macromolecular Conjugate, Adriamycin Linked to Oxidized Dextran, in Rat and Mouse Bearing Tumor Cells.

Abstract: Tissue distribution of the radioactivities after intravenous administration of [14C]adriamycin ([14C]ADM) or [14C]ADM linked to oxidized dextran ([14C]ADM-OXD) in mouse bearing Lewis lung carcinoma (LLC) and rat bearing Walker 256 carcinosarcoma was studied. ADM conjugated with OXD increased plasma half-life and gave high area under the plasma concentration-time curve (AUC). The AUC values were 13.0 and 5.8 times higher than those of the [14C]ADM group in mice and rats, respectively. In the tumor tissues, AUC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We employed Schiff base formation method for DA5018 conjugation because it has been shown to be effective for the conjugation of drugs having primary amine group to the aldehyde group of oxidized dextran (Muenchika et al 1994). Prior to conjugation to DA5018, therefore, oxidized CMD (OCMD) was prepared.…”
Section: Effect Of Chemical Modification On the Pharmacokinetics And mentioning
confidence: 99%
See 1 more Smart Citation
“…We employed Schiff base formation method for DA5018 conjugation because it has been shown to be effective for the conjugation of drugs having primary amine group to the aldehyde group of oxidized dextran (Muenchika et al 1994). Prior to conjugation to DA5018, therefore, oxidized CMD (OCMD) was prepared.…”
Section: Effect Of Chemical Modification On the Pharmacokinetics And mentioning
confidence: 99%
“…[ 14 C]CMD, [ 14 ]OCMD, and [ 14 C]OCMD-drug conjugates were synthesized by previously reported methods (Muenchika et al 1994;Ueda et al 1989) with slight modi cations. Brie y, for the preparation of [ 14 C]CMD, 100 mg of dextran T-70 and 200 mg of monochloroacetic acid, containing 37 MBq of [ 14 C]monochloroacetic acid, were dissolved in 0.33 ml of distilled water, and 0.5 ml of 10 M NaOH solution was added.…”
Section: Preparation Of [ 14 C]cmd [ 14 C]ocmd and [ 14 C]ocmd-drugmentioning
confidence: 99%
“…Furthermore, the dextran–doxorubicin conjugate also showed a different biodistribution profile from that of free doxorubicin. In mice and rats, plasma and tumor levels of the conjugate were higher than those of the free drug 44–45. Tissue distribution studies also showed that dextran–doxorubicin conjugate accumulated more in tumor tissues almost twice as much as free doxorubicin but very less in heart and skeletal muscles.…”
Section: Dextran–doxorubicin Conjugatementioning
confidence: 95%
“…In mice and rats, plasma and tumor levels of the conjugate were higher than those of the free drug. [44][45] Tissue distribution studies also showed that dextran-doxorubicin conjugate accumulated more in tumor tissues almost twice as much as free doxorubicin but very less in heart and skeletal muscles. Therefore, a different pattern of in vivo antitumor activity with respect to biodistribution of the conjugate as compared to free doxorubicin was suggested.…”
Section: Protection Of Conjugated Drugs From Biodegradationmentioning
confidence: 98%
“…On the contrary, Dex-DOXO accumulated in heart and muscles is remarkably less than free DOXO. A comparative study performed with radiolabeled drug conjugate (Dex-14 C-DOXO) of radiolabeled polymer conjugate ( 14 C-Dex-DOXO) suggested that after accumulation in the tumor DOXO was released and then the polymer chains with low drug content were cleared by kidney ultrafiltration [111].…”
Section: Doxorubicinmentioning
confidence: 99%